Pelayanan Pemadaman Api Dinas Pemadam Kebakaran dan Penyelamatan Kota Palu - Safana, Nabila; Septiara, Siti Anadya; Asran, Asran; Mustainah, Mustainah; Kurnia, Intam; Haryono, Dandan (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
This study aims to analyze the quality of fire extinguishing services provided by the Palu City Fire and Rescue Service based on SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results show that the service provided by Palu City Fire and Rescue is generally responsive and professional, especially in terms of reliability and responsiveness. However, there are still challenges in the availability of facilities and infrastructure, accessibility in public spaces, and community awareness regarding the priority of emergency vehicles. The main supporting factors are the competence and spirit of the personnel, government support, and inter-agency coordination. This research recommends improving facilities, conducting regular training, and socializing to the community to enhance the standard of public service by Palu City Fire and Rescue in disaster management